Assessment of Depression Disorder among Recovered Nurses from Covid-19 - Alaa Kadhim Raheem, Ayad Majid Mousa (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: The present study aims to assess depression disorder among recovered nurses from COVID-19 in Babylon Governorate Hospitals and to find out the relationship between depression disorder and demographic characteristics, which include age, gender, marital status, type of family size, education level, and years of experience in a health setting. Methods: A descriptive correlation design used in the present research established that for a period from October 10th, 2021 to March 20th, 2022. The study used a probability (convenient) samples of 143 nurses who recovered from COVID-19 and were drawn from wards of educational and non-educational hospitals. The instruments of the research are adopted and modified for the purpose of this research. Results: The current study showed that less than three-quarters (102, or 71.3%) of those aged (19–29) years of age of age, and more than two-thirds (94, or 65.7%) were female. Regarding marital status, more than half of the sample of 81 (56.6%) were single, and concerning family size, less than two thirds of 89 (62.2%) were small less than six individuals. In relation to educational level, more than a fifth (58, or 40.6%) were diplomas in nursing. It also revealed that about two thirds (93, or 65%) had had (1–5) years of experience in a health setting. Conclusions: Moderate depressive disorder was more prevalent in recovered nurses from the age group (19–29), specifically females, and they had served in health institutions for 1–5 years. Recommendations: Researchers must invest more in studies to measure a larger population to generalize the results. The Department of Continuing Medical Education must provide psychological support for recovered nurses from COVID-19, especially female nurses. Increased efforts should be made to hold epidemiological training courses on how to deal with transmissible viruses, as well as to understand their dangers and modes of transmission.